GEDUNG KOMUNITAS SASTRA FIKSI KREATIF DI MAKASSAR DENGAN PENDEKATAN ARSITEKTURE KUBISME - Sulthan, Silmi; Rahayu, Irma; Mutmainnah, Mutmainnah (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2014)
Planning and designing are aimed to the creative literary fiction community building in Makassar with Cubism architecture approach, this design is limited to a few problems such as the problem of architectural, location and footprint, the prospect physical design of the building, the need for space (layout), structure, materials, and equipment building so that, it can indicate the identity of what its contain, while the methods are literature studies, comparative studies, (Form obtained by comparing studies on similar projects or who have in common with creative literary fiction community building). The results of the design is creation of infrastructures to facilitate the public to channel their talents and interests in the field of literature, especially literary function and also facilitates and encourages reading by providing the quality of reading source which are cheap and reachable by all people.